Julius Caesar - Bruns, Roger; Schlesinger, Arthur Meier, 1917- (New York : Chelsea House, 1987)
A biography of the Roman general and statesman whose brillant military leadership helped make Rome the center of a vast empire.
Includes bibliographical references (p. 108) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
7.9
7.9
Keywords: Caesar, Julius -- Juvenile literature; Caesar, Julius; Caesar, Julius; Generals -- Rome -- Biography -- Juvenile literature; Heads of state -- Rome -- Biography -- Juvenile literature; Generals; Heads of state; Generals -- Biography; Heads of state -- Rome -- Biography; Rome -- History -- Republic, 265-30 B.C. -- Juvenile literature; Rome -- History -- Republic, 265-30 B.C.; Rome -- History